Taraxacum jacuticum Tzvelev - Kirschner, Jan; Štěpánek, Jan (Zenodo, 2023)
28. Taraxacum jacuticum Tzvelev in Tzvelev & Jurtzev (1984: 195) Type :—[RUSSIA, Sakha Republic] Jakutia, Yanskiy raion, dolina reki Sartang, u pos. Bala, zlakovo-osochkovaya step [district of Jana, Sartang River valley, near the village of Bala, a grass-sedge steppe], 29 Jun 1965, V. I. Perfil’eva (LE, no. det. 6050, holotype). Etymology :—After Yakutia, the Sakha Republic. Plants small, usually 6–10 cm tall, later to 15 cm tall. Plant base with a slightly developed tunic, arachnoid among petiole bases. Petiole very narrow, unwinged, purple. Leaves subglabrous, slightly greyish green, outer and middle leaves 4.5–6 × 1–1.5 cm, oblanceolate, pinnatilobed to pinnatisect, terminal segment triangular to helmet shaped, usually ca. 1 × 0.8–1.0 cm, usually subobtuse, lateral segments in 2–3 pairs, narrowly lingulate-triangular, subrecurved, not very acute, ± entire or with sparse basal teeth, interlobes entire; inner leaves (prevailing in the type plants) up to 10 × 2 cm, with terminal segment elongated, acute to acuminate, 1.5–2 × ca. 1.0– 1.3 cm, basal lobules patent, acute, lateral segments 3–4 patent to subrecurved, acute, ± entire, interlobes entire. Scape green to purplish green, sparsely arachnoid, ± overtopping leaves. Capitulum yellow or pale yellow, ca. 2.5 cm wide. Involucre ca. 8 mm wide and rounded at base. Outer phyllaries ca. 11–13, slightly imbricate, appressed, ovate-lanceolate to lanceolate, 4.5–5.5 × 2–2.5 mm, not exceeding 1/2 of the inner phyllaries, surface light green to pale green, border well developed, whitish, 0.20–0.25 mm wide, margin ciliate, apex darker coloured, blackish corniculate; inner phyllaries 12–13 mm long, ± corniculate. Outer ligules probably flat, striped black-purple outside. Stigmas light greenish, with a dark pubescence outside. Pollen present, pollen grains irregular in size. Achenes deep red-brown, 3.2–3.5 × 0.6–0.75 mm, body subsparsely covered with broad short subpatent to erect-patent spinules and short squamules, gradually narrowing into a thin cylindrical cone ...